Healthy lifestyle behaviors and hypertension among older adults in the United States (NHANES 2007-2010): Are there differences by race and ethnicity? - Philip M. DiMura; Margaret Gates; Lenore Gensburg; Elizabeth Vasquez (Journal of Aging Research And Healthcare, 2016)
Using NHANES 2007–2010, this cross‑sectional study examines associations between healthy lifestyle behaviors and hypertension among older U.S. adults, stratified by race and ethnicity. It explores how activity, diet, weight, and smoking patterns relate to blood pressure burden across groups. Findings inform tailored prevention strategies and equitable cardiovascular risk reduction.
Keywords: hypertension